IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PEMENUHAN HAK-HAK PENDIDIKAN PENYANDANG DISABILITAS DI KABUPATEN ENREKANG - Mustanir, Ahmad; Rahmat Razak, Muhammad Rais; Herman; Asrifan, Andi (re-JIEM (Research Journal of Islamic Education Management), 2021)
This study aims to determine the implementation of government policies in Enrekang Regency, to find out the fulfillment of the rights of persons with disabilities and to find out how much the implementation of government policies towards the fulfillment of the rights of persons with disabilities in Enrekang Regency